EFEKTIVITAS Trichoderma asperellum TKD DENGAN MEDIATOR PUPUK KANDANG UNTUK MENGENDALIKAN PENYAKIT LAYU FUSARIUM PADA TANAMAN CABAI MERAH (Capsicum annum L.) - Antari, Nyoman Mega; Darmayasa, Ida Bagus Gede; Hardini, Junita (SIMBIOSIS; Vol 8 No 2 (2020)DO - 10.24843/JSIMBIOSIS.2020.v08.i02.p02, 2020)
Red pepper is agricultural products in Indonesia which is often attacked by fusarium wilt disease due to the fungus Fusarium oxysporum f.sp. capsici , so in this study aims to control of fusarium wilt disease using Trichoderma asperellum TKD with mediator of manure. Method in this study is RAL (Completely Randomized Design) with 7 treatments P1 = Control I (without treatment); P2 = Control II ( F.oxysporum f.sp. capsici (disease)); P3 = disease + T. asperellum TKD 10 mL; P4 = disease + T. asperellum TKD 20 mL; P5 = disease + T.asperellum TKD 30 mL; P6 = disease + T. asperellum TKD 40 mL; P7 = disease + T. asperellum TKD 50 mL. The results showed that T.asperellum TKD was able to inhibit F.oxysporum f.sp. capsici in in vitro by 100%. The highest percentage of fusarium wilt disease (100%) is shown in plants that are only given F.oxysporum f.sp. capsici and without T. asperellum TKD, as well as plant height, total of fresh and dried leaves in plants added by T. asperellum TKD is better compared to plants that are not given T. asperellum TKD. The best plant height, number of freh leaves, and lowest number of dry leaves found in plants with 50 mL of T.asperellum TKD. Keywords: biocontrol, pathogenic fungi, Trichoderma asperellum TKD